Plant-based diet dan sindrom metabolik: uji pendahuluan pada komunitas plant-based diet Bandung - Lubis, Leonardo; Luftimas, Dimas Erlangga; Faiza, Tiara; Fatimah, Siti Nur; Fitria, Nita; Purba, Ambrosius (Jurnal Gizi Klinik Indonesia, 2024)
Association between plant-based diet and metabolic syndrome: a pilot study on Bandung plant-based diet communityBackground: Metabolic syndrome is a cluster of disorders related to cardiometabolic abnormalities that are experienced by two out of five people in Indonesia. Miscellaneous factors increase the risk of metabolic syndrome, including improper diet. Plant-based diets are expected to lower the risk of metabolic syndrome.Objective: The study investigated the association between a plant-based diet and metabolic syndrome.Methods: A cross-sectional study design was conducted on 60 subjects, consisting of 20 subjects who applied the plant-based diet and 40 subjects who did not apply the plant-based diet. Visceral fat rating, body mass index, blood pressure, fasting blood glucose, triglyceride, and HDL were also measured to identify the amount of metabolic syndrome indicators that occurred in each subject. Data was analyzed using a parametric independent sample t-test, non-parametric Mann-Whitney U, and Chi-Square tests.Results: Non-parametric test analysis in fasting blood glucose showed a significant result (p=0.022), but not in other metabolic syndrome indicators, as well as the Chi-Square test (p=1.000).Conclusions: This study found no association between a plant-based diet and metabolic syndrome.